Abrikossoff's tumor: report of a rare tumor and its unusual vulvar location - Luciana Leite Crivelin; Marilda Aparecida Milanez Morgado de Abreu (Sociedade Brasileira de Patologia Clínica, 2014)
The first report of granulosa cell tumor occurred in 1926, by Abrikossoff, after whom it was named "Abrikossoff's tumor". It is a benign, uncommon neoplasm, most frequently observed in the head, neck and tongue, being found in the vulva only in 6%-7% of the cases. Its histogenesis is uncertain, probably linked to Schwann cells. The treatment is surgical, with good prognosis. Relapses may occur, and there are descriptions of malignant transformation in the literature. The objective of this paper is to describe a case of granular cell tumor located in the vulva.